Methane emission estimates using chamber and tracer release experiments for a municipal waste water treatment plant - Yver Kwok, Camille; Müller, D.; Caldow, C.; Lebègue, B.; Mønster, J. G.; Rella, C. W.; Scheutz, C.; Schmidt, Martina; Ramonet, M.; Warneke, T.; Broquet, G.; Ciais, P. (Atmospheric measurement techniques, 2015)
This study presents two methods for estimating methane emissions from a waste water treatment plant (WWTP) along with results from a measurement campaign at a WWTP in Valence, France. These methods, chamber measurements and tracer release, rely on Fourier transform infrared spectroscopy and cavity ring-down spectroscopy instruments. We show that the tracer release method is suitable for quantifying facility- and some process-scale emissions, while the chamber measurements provide insight into individual process emissions. Uncertainties for the two methods are described and discussed. Applying the methods to CH4 emissions of the WWTP, we confirm that the open basins are not a major source of CH4 on the WWTP (about 10 % of the total emissions), but that the pretreatment and sludge treatment are the main emitters. Overall, the waste water treatment plant is representative of an average French WWTP.
Gesehen am 05.06.2020